A Culture of Future Planning: Perceptions of Sexual Risk Among Educated Young Adults. (October 2014) - Cheney, Ann M.; Ostrach, Bayla; Marcus, Ruthanne; Frank, Cynthia; Ball, Cassandra; Erickson, Pamela I.
In this study we examined how social processes, specifically the acquisition of postsecondary education and capital, shaped perceptions of sexual risk and impacted sexual practices and sexual health among young adults. Using qualitative research methods we collected and analyzed data among students attending a 4-year university in the northeastern region of the United States over a 1-year period. By analyzing participants' narratives, we found that the reproduction of shared norms and values encouraged educated young adults to focus on educational and professional success, pressing many of them to be concerned about preventing pregnancy rather than preventing disease transmission, and increasing their risk for sexually transmitted infections, including HIV/AIDS. Sexual-health educators need to address how social processes shape sexual practices, encourage educated young adults to challenge unequal gender expectations, and consider how sexually transmitted infections might also interfere with life plans.